2014
DOI: 10.1097/rct.0b013e3182ab384a
|View full text |Cite
|
Sign up to set email alerts
|

CT of Preoperative and Postoperative Acetabular Fractures Revisited

Abstract: Although reoperation rate is low after fixation of AFs, CT is required to identify those requiring reintervention. However, postoperative CT should be used judicially, only in patients presenting with complex acetabular fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Controversy exists about routine use of postoperative CT scans, because of the costs, radiation exposure and limited clinical consequences. [12,13] Nevertheless, routine postoperative CT scans have been used in large studies for assessing postoperative reduction, determining patient’s prognosis, and the evaluation of the surgical techniques. [9] There is no difference in radiation exposure between 3DCT and 2DCT fracture assessment, because both measurement techniques are based on the same CT data.…”
Section: Discussionmentioning
confidence: 99%
“…Controversy exists about routine use of postoperative CT scans, because of the costs, radiation exposure and limited clinical consequences. [12,13] Nevertheless, routine postoperative CT scans have been used in large studies for assessing postoperative reduction, determining patient’s prognosis, and the evaluation of the surgical techniques. [9] There is no difference in radiation exposure between 3DCT and 2DCT fracture assessment, because both measurement techniques are based on the same CT data.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies show poor correlation between the degree of articular reduction as seen on postoperative CR and clinical outcome (13,21). Jaskolka et al shows that as much as 44% of patients with acetabular fractures has significant findings on conventional CT, signifying either imperfect fracture reduction, intra-articular fragments, or hardware complications, less than half of these findings are visualized with CR (7). The advantage with CT when assessing hardware positioning and fracture reduction is well described regarding acetabular fractures (7) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of acetabular joint congruency with both CR and LDCT in this study was based on criteria described by Matta, which were developed for CR (13). Recent studies have proposed revised criteria for significant findings in postoperative CT (7). A review article by Dodd et al concluded that there is a lack of reproducible description methods when dealing with radiographic criteria for assessing displacement of acetabular fractures, the one described by Matta et al being used in the majority of studies (13,29).…”
Section: Discussionmentioning
confidence: 99%
“…Jaskolka et al demonstrated that 44% of patients had significant post-operative CT findings defined as imperfect alignment, 2 or more intra articular fragments, or hardware complications. Out of those with significant post-operative findings, 92% were complex acetabular fractures defined as anything more than a simple Letournel/Judet posterior wall or anterior column fracture [7]. Furthermore, this case would have been an excellent opportunity for intraoperative cone beam tomography imaging and could have possibly avoided a return trip to the OR to remove the intra-articular loose bodies.…”
Section: Discussionmentioning
confidence: 99%